PERCERAIAN KARENA KETIDAKHARMONISAN RUMAH TANGGA YANG DIDASARI KAWIN PAKSA (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
Based on this research, the results obtained that the case of divorce is called divorce on the basis of forced marriage in case Number 348 / Pdt.G / 2011 / PA.Psp is that the Petitioner sued the Respondent on the grounds that during the household life the Petitioner and Respondent had never living in harmony because of marriage between the Petitioner and the Respondent at the insistence or coercion of the Respondent's family. The Petitioner gave a statement to the Judge that the marriage of the Petitioner and the Respondent was not from the wishes of the Petitioner himself but rather from coercion or pressure from the Respondent's family, then the Petitioner also gave a witness to the judge to corroborate the Petitioner's statement that the Petitioner was indeed forced into marriage